Implementation of the Blue Economy Concept of Traditional Fisheries Management in the Conflict Zone, on the Coast of the Kebintik Village, Pangkalan Baru District, Central Bangka Regency - Endang Bidayani; Reniati Reniati; Agung Priyambada (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Sea is an open access resource, so it has the potential to cause a conflict of interest in its use. One of the conflict zones between smallholder tin miners and traditional fishermen in the Province of the Bangka Belitung Islands is on the coast of the Kebintik Village, Pangkalan Baru District, Central Bangka Regency. Blue economy is an environmentally friendly management concept to ensure the sustainability of fish resources. For this reason, this research aims to examine on the implementation of the blue economy concept of traditional fisheries management in conflict zones. This research method is a survey method. The research has been conducted in Kebitik Village, Pangkalan Baru District, Central Bangka Regency. Sampling used census sampling technique. The population in this study are traditional fishermen who have operated for more than a year in coastal areas as many as 30 people. Data collection methods in this study include primary data and secondary data. Primary data collection using questionnaires, observation and documentation. Secondary data collection through literature study. The data analysis method used is descriptive method. The implementation of the blue economy concept of traditional fisheries management in the conflict zone which includes the principles of resource efficiency, zero waste, social care and investment, innovation and adaptation is 100%.